Results of the metallographic study of blacksmithing items from the excavations at Podgory V settlement on the Samara Bend - Kondrashin Vitaly V.; Myshkin Vladimir N. (Поволжская археология)
The article presents the results of metallographic analysis of blacksmithing items, found during excavations at the Podgory V settlement, located on the Samara Bend. The materials of the 1999-2001 excavations are represented by items and sets (including burials ones) belonging to the period from the Early Iron Age to the Middle Ages. The most representative materials are related to the Imenkovo culture of the IV–VII centuries. The sample of ferrous metal artifacts subjected to metallographic study amounted to 21 pieces: knives, awls, sickle, arrowhead, earring with a polyhedron, fixing ring, fire lighter and plate. The metallographic collection included rod-shaped objects, some of which were identified as semi-finished products (metal raw material). It was found that the main material for most of the items was low carbon steel. Packing of blanks was often used and local cementation was applied. The share of heat-treated products is high, signs of high-temperature forging were recorded. The revealed characteristics of forgings from Podgory Vsetlement, in general, correspond to the level of development and technological appearance of East European early medieval ironworking. However, there were also found such features that distinguish the “Podgory” sample from the archaeometallographic collections of other Middle Volga sites of the Early Middle Ages. The peculiarity manifested itself in the use of the characteristic twisting technique of two- or multilayer blanks.